Investigations for Acromioclavicular Joint Injuries - Tanvi Radadiya; Noel Samuel Macwan (Understanding Acromioclavicular Joint Injuries and its Management, Edition 1, 2024)
Imaging studies are required when the patient’s medical history and physical examination point to a potential AC joint damage. One-third to one-half of the X-ray penetration required for glenohumeral joint exposure is necessary for an accurate radiographic examination of the AC joint. On anteroposterior radiographs, the AC joint’s configuration varies greatly. A coracoid fracture should be suspected when there is a complete dislocation of the AC joint but a normal CC interspace. Due to its high cost and restricted local availability, MRI is not practical for everyday usage. Radiological investigation giving useful information on the kind and extent of AC joint injuries plays a vital role in planning the management. Correct X-ray views are required for the investigation of the AC Joint Injury. Anteroposterior view, Velpeau view and the Zanca are important views when plain radiographs are used. MRI not being the gold standard method in diagnosing AC Joint Injury still can be very helpful in case there are small injuries not diagnosed through X-Ray. For ruling out other injuries, additional X-ray views like axillary and AP shoulder views are needed for better diagnosing the injury.